Note on the Zinc Deposits of Southern Missouri - Rossiter W. Raymond (The American Institute of Mining, Metallurgical, and Petroleum Engineers, 1880)
THE lead-mining industry of Missouri, as of other parts of the Mississippi basin, appears to have been paralyzed by the shock of competition with the mines of the States and Territories further west. It is difficult for establishments working galena ores, too poor in silver to pay for extracting it, to compete with the producers of the argentiferous carbonates of Utah and Colorado, who look upon their lead as a byproduct of little value, and are satisfied if it pays the charges of transportation, or the loss in smelting for silver. But simultaneously with this depression in the lead-mining of the Mississippi States, the development of new zinc deposits has caused a notable revival in the mining of zinc ores. There has recently been a sudden and strong rise in the price of spelter, which, though probably to a large extent temporary in character, has given important encouragement to prospectors and miners. Apart from the general recovery of business in the United States from the prostration of the past six years, the cause of the advance in spelter has been the falling off in production, resulting from the shutting down of several leading Western works,-the Martindale and Carondelet works, at St. Louis, and the Consolidated Company in Kansas. At the same time, the principal works at La Salle, Ill., were undergoing repairs, and produced less than usual, while the sheet-mill of Matthieson & Hegeler, at that place, was running as usual; so that this concern, ordinarily a large producer, entered the already depleted market as a buyer. These causes are in their nature transitory, and it is quite likely that spelter will be superabundant in a few months. Having lately received from a well-informed Missouri corres¬pondent some samples of the zinc ores and a general account of the ore deposits of Southwest Missouri, I have thought that it might interest the Institute to examine these specimens, and to hear such brief statements concerning the region as I am able, upon good authority, though without the aid of any personal investigation on the spot, to give. The zinc-bearing territory in Southwest Missouri appears to be very extensive; that is to say, zinc ores have been mined during the last year at various points throughout a district extending from the eastern edge of Kansas, west of Joplin, to a line some 50 miles east